Profile of darunavir in the treatment of HIV-infected pediatric and adolescent patients - Dobroszycki J; Abadi J; Wiznia A; Rosenberg MG (Dove Medical Press, 2011)
Joanna Dobroszycki, Jacobo Abadi, Andrew A Wiznia, Michael G RosenbergDepartment of Pediatrics, Division of Infectious Diseases, Jacobi Medical Center, Bronx, NY, USAAbstract: The introduction of protease inhibitors (PI) containing antiretroviral regimens in the treatment of HIV infection in infants, children, and adolescents has dramatically decreased morbidity and mortality. Darunavir, the latest PI to be FDA approved for pediatric patients older than 6 years and currently the preferred PI for use in adult patients, was added as an alternative PI for use in children based on a combination of data from both adult and pediatric trials. This review of darunavir in the treatment of HIV-infected children and adolescents looks at the major published clinical trials findings, pharmacokinetic and resistance studies, and preliminary data on use in younger children.Keywords: darunavir, HIV, protease inhibitor